Preparation of high quality ferrovanadium nitride by carbothermal reduction nitridation process - Wu Y.D.; Zhang G.H.; Chou K.C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
High quality ferrovanadium nitride was prepared successfully by carbothermal reduction nitridation process by using V2O5 and Fe as the raw materials. The effects of reaction temperature and C/O molar ratio (content of O is defined as the oxygen in V2O5) on the quality of ferrovanadium nitride were investigated in detail. It was demonstrated that C/O molar ratio had a great influence on the residue carbon, as well as the nitrogen content in the final products. It was found that the nitrogen content of the final product achieved 11.52% when the C/O molar ratio was 90% of the stoichiometric value. However, the nitrogen contents of the final products decreased with the further increase of C/O molar ratio. For the temperature higher than 1773 K, Fe became liquid phase and surrounded the solid V(C, N, O) particles tightly. The formation of liquid Fe was beneficial for the further removal of oxygen atoms left in the V(C, N, O) lattice, since it provided a liquid tunnel for carbon diffusion which greatly enhanced the reaction kinetics. From the results of X-ray diffraction (XRD) and thermodynamic calculations, phase evolution sequence of V2O5 can be obtained as: V2O5→VO2→V2O3→V(C, N, O). Moreover, the kinetic process from V2O3 to VN was studied and the results shown that the reaction rate can be described by Jander diffusion model with the extracted activation energy of 188.173 kJ/mol.